Analisis Pengaruh Penerapan Total Quality Management Terhadap Kinerja Operasional Pada Koperasi Simpan Pinjam Setiawan Bejawa - Peba, Lensiana Rawi; Langga, Lambertus; Tanusi, Gabriel (Program Studi Manajemen Universitas Flores, 2021)
This study aims to find out how big the Analysis of Implementation of Total Quality Management on Operational Performance in Cooperative Save Borrow Setiawan Bajawa.This research was conducted on members of the Setiawan Bajawa Cooperative, with using quantitative attachment with data collection is carried out by how to spread kusioner as many as 30 respondents and analyzed using multiple liner regression through spss progran with validity and reliability tests.The results of the analysis showed that the indicators used valid to measure existing variables. the results of subsequent analysis found that of the four variables used, it can be interpreted that in the regression equation, a constant value of 13,766 with a coefficient of variable member satisfaction 2,229, employee empowerment 2,461, increased 1,748, management based on facts 1,788.The results of the analysis also showed that the four variables used in this study can be obtained by 0.517 or 51.7 %, this indicates that the percentage of the influence of member satisfaction, member empowerment, sustainable quality and fact-based management of 51.7%., while 48.3% is described by other variables not included in this model